2012
DOI: 10.1111/j.1475-3995.2012.00869.x
|View full text |Cite
|
Sign up to set email alerts
|

Semidefinite relaxation for linear programs with equilibrium constraints

Abstract: In this paper, we present a semidefinite programming (SDP) relaxation for linear programs with equilibrium constraints (LPECs) to be used in a branch‐and‐bound (B&B) algorithm. The procedure utilizes the global optimal solution of LPECs and was motivated by the B&B algorithm proposed by Bard and Moore for linear/quadratic bilevel programs, where complementarities are recursively enforced. We propose the use of the SDP relaxation to generate bounds at the nodes of the B&B tree. Computational results compare the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…As an option, we can smoothen the valuation function by using a smooth approximation function. The model ( 28) is an MPEC, and many efficient numerical algorithms have been proposed for solving MPEC (see, e.g., Facchinei et al, 1999;Fampa et al 2013;Fletcher et al, 2006;Gabriel et al, 2010;Hoheisel et al, 2012Hoheisel et al, , 2013Kim et al, 2020;Luo et al, 1996;Scholtes, 2001). Dempe and Dutta (2012) study the equivalence relationship between the bi-level program and its MPEC reformulation at global/local optimal solutions.…”
Section: Solutions To Focus Programming Models Under the Negative Eva...mentioning
confidence: 99%
“…As an option, we can smoothen the valuation function by using a smooth approximation function. The model ( 28) is an MPEC, and many efficient numerical algorithms have been proposed for solving MPEC (see, e.g., Facchinei et al, 1999;Fampa et al 2013;Fletcher et al, 2006;Gabriel et al, 2010;Hoheisel et al, 2012Hoheisel et al, , 2013Kim et al, 2020;Luo et al, 1996;Scholtes, 2001). Dempe and Dutta (2012) study the equivalence relationship between the bi-level program and its MPEC reformulation at global/local optimal solutions.…”
Section: Solutions To Focus Programming Models Under the Negative Eva...mentioning
confidence: 99%
“…The research in this field is still active as shown, for example, in the recent works of Anstreicher (), Burer and Vandenbussche (), Fampa et al. (), Rendl et al. (), Saxena et al.…”
Section: Introductionmentioning
confidence: 99%
“…Other strategies to solve bilevel problems include: bundle type algorithms [89], semi-definite relaxations [90], penalty function based methods [91,92,93], Benders decomposition [94]. Cutting-plane approaches [95,96,97] have received attention recently because they can handle lower-level problems with integer variables -solvers were developed by [98,99].…”
Section: Solving Bilevel Optimizationmentioning
confidence: 99%